Changes in social capital of rice farmers: An antropological study for buginese farmers - Pawalluri, Thamrin; Salman, Darmawan; Fahmid, Imam Mujahidin; Marmin, Hidayat; Amir, Arfenti; Enre, Amruddin Ambo (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2021)
Local institutions that encourage self-organization to achieve shared-goals is a characteristic of social capital. In Bugis society, there is a social capital in farming communities called tudang sipulung, meaning “sitting together for deciding various matters related to farming”. However, tudang sipulung has been transformed. This study aims to determine causes, processes, and consequences of social change in tudang sipulung tradition. The data from this case study were collected by using in-depth interviews, observations, and document review. The results show that the cause of change was an abandonment of traditional rituals in farming because farmers consider that such rituals delay activities and require more cost, so to reduce the effectiveness and efficiency. In addition, there is also a shift in the position of actors, where the schedule of the planting which was previously determined by indigenous knowledge possessed by traditional leaders, changed to the role of climatologists and officers from the government. The process of social change takes long and slow along with the social dynamics of the rice farming community which makes tudang sipulung tradition as a place to work together to achieve shared-goal for farmers. Nevertheless, the process of social change has consequences for the elimination of kindness to each other and lack of trust among farmers.